Underground Activities and Labour Market Performance - Ann-Sofie Kolm; Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2018)
We build a general equilibrium model in terms of a search and matching model with an informal sector. We consider the impact of the traditional policy instruments considered in the tax evasion literature, such as changes in the tax- and punishment system as well as changes in the employment protection legislation and concealment costs, on labour market outcomes. To this end, we set-up a model which allows workers to allocate their search for formal and informal sector jobs optimally. We calibrate and simulate the model to fit the North and the South of Europe, where the share of informal sector workers is equal to three percent in the North and more than 4 times as high in the South. We consider the impact of concealment costs, as there are large differences in terms of tax administration procedures between the South and the North, in terms of that Northern countries make more extensively use of third-party reporting. We also examine whether stricter employment protection legislation in Southern Europe may explain the observed fact.
hdl:10398/9588
Keywords: E24; E26; H26; 330; informal economy; tax policy; tax evasion; Northern Europe; Southern Europe